Detection of Potential Pneumonia-Causing Bacteria Found in Nebulizers in Iligan City Hospitals: Some Implications on Infection Control (Asia Pacific Journal of Social Innovation, 2024)
In the third national prevalence survey of infection in hospitals, pneumonia was the third most common (13.9 per cent) acquired infection in acute hospitals (Hospital Infection Society/Infection Control Nurses Association, 2007). Hospital acquired pneumonia is associated with crude mortality rates up to 70% and attributable mortality rates as high as 33% to 50%. Pneumonia is one of the top ten causes of deaths in the Philippines. Inhalation therapy equipment such as nebulizer may potentially act as a vector of hospital acquired pneumonia. The major mechanism by which bacteria are disseminated is aerosolization of organisms in particle sizes that are sufficiently small to be deposited in terminal lung units. Nebulizers create aerosols of minute droplets that penetrate deeply into the narrowest airways and thus present a significant problem. This is especially so for small - volume medication nebulizers (Botman and de Krieger, 1987). The main purpose of this study is to conduct a bacteriologic assessment of the different parts of the nebulizers in selected wards of Iligan City Hospitals. Acquisitions of samples were obtained through swabbing at different parts of the nebulizers specifically the air filter and compressor port from different wards of ligan City Hospitals. Swab samples were subjected to the conventional method of identification of bacterial species. Bacillus sp., Streptococcus sp., and Staphylococcus sp. (pathogonie and nonpathogenic) were among the identified bacterial species. Between the air filter and compressor port, the latter yielded the highest number of bacterial species. Moreover, the parts of the nebulizer are not dependent on each other with respect to the total number or types of bacteria prosent. Bacteria are the most common causes of pneumonia. The most common organisms that cause pneumonia include Streptococeus (S) pneumoniae (also called pneumocoecus, Staphylococeus (S.) aurous, Streptococcus pyogenes or Group A streptococus and to a lesser degree. Bacillus anthracis may also cause Typical pneumonia. Based on the findings of this study, it is recommended that proper care and maintenance should be observed to reduce if not, eliminate potential source of nosocomial pneumonia that may pose a threat to patient's health condition.